Proposed New Architecture Of Overlay Network Of Distributed Hash Table (International Journal of Engineering and Computer Science, 2017)
This paper proposes the new architecture of overlay network of Distributed Hash table (DHT). We introduce a new MultiChord Protocol which is another variant of Chord Protocol defined over overlay network of Distributed Hash table. MultiChord inherits basic properties of Chord protocol with some added new features.